Yup’ik perspectives on climate change: “The world is following its people” - Fienup-Riordan, Ann (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2010)
AbstractThe Nelson Island Natural and Cultural History Project originated in the desire of community members in the Yup’ik villages of Chefornak, Nightmute, Toksook Bay, Tununak, and Newtok to document and share their history with their younger generation. To do so, they invited non-Native scientists to join them in village gatherings as well as on a three-week circumnavigation of Nelson Island (Alaska), during which elders reflected on changes in weather patterns, animal migrations, sea-ice conditions, and related harvesting activities. To date, a defining feature of our conversations has been the integrated way in which information is shared and elders’ reticence to distinguish between human impacts on the environment and the “natural” effects of climate change.